2020
DOI: 10.1071/an17905
|View full text |Cite
|
Sign up to set email alerts
|

Faba bean-rapeseed silage as substitute for Italian ryegrass silage: effects on performance and milk quality of grazing dairy cows

Abstract: Three trials were conducted to study the effect of including in the ration of dairy cows the intercrop faba bean-rapeseed or Italian ryegrass silages on feed intake, milk quality and enteric methane emissions. Ten lactating Holstein cows, randomly allocated in two groups, were used in each trial in a crossover design. Dry matter intake and milk yield were recorded daily for each data period. Milk was sampled for analyses three times per period. Enteric methane emission was estimated applying a model that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…This could be because the content of WSC in the mixed silage was optimally complementary at this ratio, which provided sufficient fermentation substrate for the growth and reproduction of LA bacteria, thereby increasing the content of LA in the silage and ultimately reducing the pH. This result was consistent with the findings of Jiménez-Calderón et al [41].…”
Section: Effect Of Mixed Silage Of Rapeseed and Alfalfa Or M Spicatum...supporting
confidence: 90%
“…This could be because the content of WSC in the mixed silage was optimally complementary at this ratio, which provided sufficient fermentation substrate for the growth and reproduction of LA bacteria, thereby increasing the content of LA in the silage and ultimately reducing the pH. This result was consistent with the findings of Jiménez-Calderón et al [41].…”
Section: Effect Of Mixed Silage Of Rapeseed and Alfalfa Or M Spicatum...supporting
confidence: 90%
“…The protein and energy ratio of the diet or the non-degradable and degradable protein ratio in the rumen can affect the urea content in milk [37]. In a similar work [31], the milk from dairy cows fed diets based on faba bean had higher urea concentrations than those fed with diets based on Italian ryegrass silage. The high level of urea in the milk may also be related to the use of legume silages that have higher ammoniacal nitrogen contents.…”
Section: Discussionmentioning
confidence: 92%
“…Some rumen fermentation studies have shown that the differences result in lower filling and a higher rate of rumen passage, which explains a higher intake capacity in legumes than in grasses [30]. Other studies reported a significant reduction in the voluntary intake of rations based on legumes in comparison to rations based on Italian ryegrass silage [31]. This fact was attributed to the tannins of legume blooms and seeds.…”
Section: Discussionmentioning
confidence: 99%
“…as the winter crop and maize (Zea mays L.) as the summer crop. This crop rotation is very productive, but highly demanding of nitrogen that could have negative effects on soil fertility [4,5]. Therefore, more environmentally friendly alternatives must be considered.…”
Section: Introductionmentioning
confidence: 99%